A comparative exergoeconomic evaluation of biomass post-firing and co-firing combined power plants. Issue 1 (2nd January 2017) - Athari, Hassan; Soltani, Saeed; Rosen, Marc A.; Mahmoudi, Seyed Mohammad Seyed; Morosuk, Tatiana
ABSTRACT: This paper reports the results of energy, exergy and exergoeconomic analyses of biomass gasification-based power plants. Three configurations are considered: externally fired biomass combined cycle, biomass integrated co-firing combined cycle and biomass integrated post-firing combined cycle. The latter configuration is found to be more economically effective (on a large scale). The energy efficiency for the biomass integrated post-firing combined cycle plant is about 3% and 6% higher than the biomass integrated co-firing combined cycle and externally fired combined cycle plants, respectively. The parametric studies demonstrate that the energy and exergy efficiencies can be increased (for the three configurations) by raising the compressor pressure ratio; however, higher pressure ratios lead to lower values of the total product cost only for the biomass integrated post-firing plant. Increasing the gas turbine inlet temperature leads to a slight decrease in the unit product cost for the externally fired biomass combined cycle and the biomass integrated co-firing combined cycle.